ACTUAL PROBLEMATICS IN STUDIES OF CONTEMPORARY CHINESE LITERATURE - Vladimir V. Seligey (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The study of Chinese literature in the comparative perspective seems fruitful in terms of identifying universal categories of artistic thinking, which either remain unchanged, or transformed in the context of a radically different culture, which went a different way in shaping such a basic communication tool as language, preserving the system in the hieroglyphics to phonetic writing. Contemporary Chinese literature, as agreed by researchers, is generally defined as a deep synthesis of Western and traditional aesthetics of the East, but the vast majority of aspects of rethinking and representing the genetic “their” is usually left out of the attention of foreign researchers. The aim of the present study is to highlight the current trends, approaches and concepts of comparative study of modern Chinese literature, as well as to determine the outlines of modern Chinese literature as an object of comparative research in the context of the problem of the synthesis of “his” and “alien” in poetry and semantics of works of contemporary Chinese writers. The up-to-date methodology of comparative analysis of Chinese poetry in the context of world literature, the complex poetic-semantic system of classical Chinese poetry are considered in relation to the traditional categories of Western poetics: “image”, “symbol”, “allusion”, “metaphor”. Special attention is given to experimental approaches, such as J. Liu’s where comparative method was used for explaining Chinese poetry and poetics to his English audience. According to researchers, the main achievement of this work is the search for “trans-cultural and trans-historical values”. The term “post-Mao-dengizm”, coined by Chinese scholar S.Yang and the hypothesis behind it which embeds Chinese “root-seeking” and “pure literature” into the postmodern paradigm as well as its chronological framework is seen as one of the highlights of comparative oriental studies. The fruitful research, conducted by Wang Ning, elucidates an important feature of the novel “Visiting the Country of Dreams” (1993) as the creation of an individual parable and a metaphor, by means of which the author tries, through a system of symbols and metaphors, to recreate something like the history of mankind from the primitive state to modern civilization, marked with the associative ties to the Christian biblical motives, as well as to the Buddhist and Confucian discourses. Any of these experiments cannot be determined by a simple unambiguous formulation and requires an approach in the broadest perspective that takes into account the history of world literature and can comprehend the many concepts and concepts of modern and classical theory of literature.